PENGARUH EKSTRAK BIJI NIMBA (Azadirachta indica) TERHADAP PENURUNAN DERAJAT PARASIT DAN JUMLAH HEMOZOINPADA KULTUR Plasmodium falciparum - Aini, Noer; Soebaktiningsih, Soebaktiningsih; Fitri, Loeki Enggar; Kalsum, Umi; Sumarno, Sumarno (Fakultas Kedokteran Universitas Brawijaya, 2004)
Malaria infection is still one of world health’s problems that cause a high death rate (20.9% - 50%). One of the reason is Plasmodium falciparum resist to conventional anti-malarial drugs. Neem seeds extract had been reported has antimalarial effect by decreasing parasitemia, but there has not been any report on its effect in inhibition hemazoin formation. The aimof this research was to find the effect of Neem seeds extract on parasitemia and hemazoin level in Plasmodium falciparum culture. Laboratory experiment was done by using Papua isolate of Plasmodium falciparum (2300) from NAMRU 2 Jakarta. After synchronized, malarial culture was divided into 4 groups namely Control group (culture medium only), Chloroquine group, Artemisinin group, and Neem seeds extracts group. Each treatment group was devided into 5 drug doses of 6.25 µ/ml, 12.5 µ/ml, 25 µ/ml, 50 µ/ml and 100 µ/ml respectively. Parasitemia was measured by Pyridine-hemochrome methods using spectrophotometer λ560 nm. Statistical analysis was done involving one-way-ANOVA followed by Tukey HSD and Pearson’s Correlation. A significant difference was found between control and treatment groups in parasitemia and hemozoin level. Different dose in treatment groups didn’t show any significant difference in both parasitemia (p=0.99) and hemozoin level (p=0.985). Tukey test between treatment groups didn’t show a significant difference decrease of hemazoin level and parasitemia (r=0.970). The conclusion was Neem deeds extract can inhibit P. falciparum growth by decreasing parasitemia and hemazoin level. Key words: Neem seeds extract, parasitemia, hemazoin level, P. falciparum